(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This report describes a research of the qualities of soil stabilised using lime and egg shell powder. Tests were carried out to evaluate the possibility of egg shell powder in substituting lime, which can make the whole stabilisation process more cost-effective and environmentally benign. The results demonstrate that all of the treated mixtures outperformed the untreated soil in terms of strength. Egg shell powder was added to the soil in amounts of 0.5%, 1%, 1.5%, and 2% by weight. Replacement of up to 50% of the lime used for stabilisation was tested. It was discovered that replacing 25% of the lime with egg shell powder provided higher strength qualities and may be used in practise.